Optical evolution of AT 2024wpp: the high-velocity outflows in Cow-like transients are consistent with high spherical symmetry - Pursiainen, M.; Killestein, T. L.; Kuncarayakti, H.; Charalampopoulos, P.; Warwick, B.; Lyman, J.; Kotak, R.; Leloudas, G.; Coppejans, D.; Kravtsov, T.; Maeda, K.; Nagao, T.; et al. (Oxford University Press (OUP), 2025)
We present the analysis of optical/near-infrared (NIR) data and host galaxy properties of a bright, extremely rapidly evolving transient, AT 2024wpp, which resembles the enigmatic AT 2018cow. AT 2024wpp rose to a peak brightness of c=-21.9 mag in 4.3 d and remained above the half-maximum brightness for only 6.7 d. The blackbody fits to the photometry show that the event remained persistently hot (T greater than or similar to 20000 K) with a rapidly receding photosphere (v similar to 11500 km s-1), similarly to AT 2018cow albeit with a several times larger photosphere. JH photometry reveals an NIR excess over the thermal emission at similar to+20 d, indicating a presence of an additional component. The spectra are consistent with blackbody emission throughout our spectral sequence ending at +21.9 d, showing a tentative, very broad emission feature at similar to 5500 & Aring; - implying that the optical photosphere is likely within a near-relativistic outflow. Furthermore, reports of strong X-ray and radio emission cement the nature of AT 2024wpp as a likely Cow-like transient. AT 2024wpp is the second event of the class with optical polarimetry. Our BVRI observations obtained from +6.1 to +14.4 d show a low polarization of P less than or similar to 0.5 per cent across all bands, similar to AT 2018cow that was consistent with P similar to 0 per cent during the same outflow-driven phase. In the absence of evidence for a preferential viewing angle, it is unlikely that both events would have shown low polarization in the case that their photospheres were aspherical. As such, we conclude that the near-relativistic outflows launched in these events are likely highly spherical, but polarimetric observations of further events are crucial to constrain their ejecta geometry and stratification in detail.